2008
DOI: 10.1002/j.0022-0337.2008.72.9.tb04581.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Interdisciplinary Course in Information Resources and Evidence‐Based Dentistry

Abstract: The capacity to locate, access, and appraise information is an important skill required for success in dental school and beyond. An interdisciplinary course was implemented to teach first-year dental students at the University of Texas Health Science Center at Houston Dental Branch about evidence-based dentistry, search strategies, critical appraisal of the literature, and dental informatics. Students learned to develop a clinical question, conduct a search to find answers to that question, and critically appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(58 citation statements)
references
References 28 publications
2
53
0
Order By: Relevance
“…These results strongly suggest the need for designing and incorporating information literacy and integration of technology-dependent, applied research assignments into graduate-level curricula. Although some evidence exists for guidance on successful evaluation strategies during the process of developing information literacy skills [ 17 , 18 ], relatively few examples of specific courses and specific recommendations can be found [ 19 ]. The results of this study suggest that placement of ILS and ICT teaching and learning modules should be integrated and incorporated early in the graduate curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…These results strongly suggest the need for designing and incorporating information literacy and integration of technology-dependent, applied research assignments into graduate-level curricula. Although some evidence exists for guidance on successful evaluation strategies during the process of developing information literacy skills [ 17 , 18 ], relatively few examples of specific courses and specific recommendations can be found [ 19 ]. The results of this study suggest that placement of ILS and ICT teaching and learning modules should be integrated and incorporated early in the graduate curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that EBD courses can improve critical appraisal expertise. Levin et al (2008) emphasized the benefits of an interdisciplinary course that was implemented to teach first-year dental students at the University of Texas Health Science Center at Houston Dental Branch about EBD, search strategies, critical appraisal of the literature and dental informatics 16 . Thomas et al (2009) also implemented a similar course in the University of Kentucky and reported that the course was successful 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Social work students, especially those at Level 1, are more likely than health and social care students to think skills are important, that they will be able use them in employment, and that their employer also thinks digital literacy is important. Levine et al (2008) found that dentistry students value information literacy skills when the relevance to their professional practice is made clear. Edmunds, Thorpe and Conole (2012) found that ICT is perceived by students most positively in the work context.…”
Section: Discussionmentioning
confidence: 99%